Spider silk nerve graft promotes axonal regeneration on long distance nerve defect in a sheep model. (April 2021) - Kornfeld, T.; Nessler, J.; Helmer, C.; Hannemann, R.; Waldmann, K.H.; Peck, C.T.; Hoffmann, P.; Brandes, G.; Vogt, P.M.; Radtke, C.
Abstract: Peripheral nerve injuries with substantial tissue loss require autologous nerve transplantation or alternatively reconstruction with nerve conduits. Axonal elongation after nerve transection is about 1 mm/day. The precise time course of axonal regeneration on an ultrastructural level in nerve gap repair using either autologous or artificial implants has not been described. As peripheral nerve regeneration is a highly time critical process due to deterioration of the neuromuscular junction, this in vivo examination in a large animal model was performed in order to investigate axonal elongation rates and spider silk material degradation in a narrowly delimited time series (20, 30, 40, 50, 90, 120, 150 and 180 days) by using a novel spider silk based artificial nerve graft as a critical prerequisite for clinical translation. Autologous nerves or artificial nerve conduits based on spider silk of the spider species Trichonephila edulis were transplanted in a 6.0 cm nerve defect model in the black headed mutton. At each of the post-implant time point, electrophysiology recordings were performed to assess functional reinnervation of axonal fibers into the implants. Samples were analyzed by histology and immunofluorescence in order to verify the timeline of axonal regeneration including axonal regeneration rates of the spider silk implant and the autologous transplant groups. Spider silk was degraded within 3 month by a light immune response mainly mediated by Langhans Giant cells. In conjunction with behavioral analysis and electrophysiological measurements, the results indicate that the spider silk nerve implant supported an axonal regeneration comparable to an autologous nerve graft which is the current gold standard in nerve repair surgery. These findings indicate that a biomaterial based spider silk nerve conduit is as effective as autologous nerve implants and may be an important approach for long nerve defects. Abstract : Reconstruction of a 6.0 cm tibial nerve defect using a spider silk based artificial nerve implant lead to significant nerve regeneration in long term observation. Results indicate clinical and histological axonal regeneration throughout a critical nerve gap.